Trends And Issues of The Investment Legal Revolution Evidence of The Omnibus Law Job Creation (Journal of Private and Commercial Law, 2021)
The multidimensional crisis due to the COVID-19 pandemic has implications for the country's economy. Foreign investors are sought to help extinguish the threat of a deficit in state finances through foreign investment (FI). Access to investment, which was initially limited in nature, has become quite flexible due to the promulgation of the Omnibus Law on Job Creation. Legislative reform which was colored by intrigue and controversy was packaged as a way out for national development and economy, especially as a response to the prevention of the country's financial crisis. This research examines the implementation of FI regulations on the investment climate in Indonesia, especially during the period of COVID-19 pandemic and a critical narrative towards the Omnibus Law on Job Creation which represents the investment legal revolution. By using normative legal research methods, this research is expected to be able to answer the above legal issues through a statutory approach and literature law materials which include scientific works and research results. The results show that the implementation of FI regulations in Indonesia is still classified as complicated so that the effect is the low interest of foreign investors to invest their capital in Indonesia. Although the government through the Capital Investment Coordinating Board has attempted to overcome this problem by pioneering the establishment of the One Stop Integrated Service and Investment Service, the COVID-19 pandemic has made it more difficult for the realization of foreign investment in Indonesia. On the other hand, Government policy in reforming investment law in Indonesia through the Omnibus Law on Job Creation too prioritizing economic targets that are not proportional to the threat of state sovereignty and guarantee of people's welfare.